2017
DOI: 10.1016/j.micromeso.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of activated carbon discs from tar pitch and coal powder for adsorption of CO 2 , CH 4 and N 2

Abstract: We used a pitch foaming process to prepare high surface area activated carbon discs ACD with a relatively high mechanical strength (4.3 MPa) from mixtures of tar pitch and coal powders, with potassium hydroxide as a chemical activator. The two primary parameters investigated in this study were the amount of nitric acid used in the pitch pre-treatment and the size of the coal particles (0 -53 µm, 150 -250 µm, and 355 -550 µm). The pre-treatment of the pitch was observed to be critical in the production of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 52 publications
(55 reference statements)
3
34
0
Order By: Relevance
“…These stress-stain measurements show that although mesophase pitch to coal ratio did not have a significant effect on the density or total porosity of the KOH activated ACDs (refer to Table 2), the amount of coal added did have a strong influence on compressive strength of the discs with the compressive strength of ACDMP1C2 (56 ± 3 MPa) prepared with the highest concentration of coal particles more than twice the strengths measured for ACDMP1C1 (27 ± 1 MPa) and ACDMP2C1 (24 ± 2 MPa). In fact, as shown in Table 3 all three KOH activated MP + coal ACDs produced in this study exhibited much greater compressive strengths than similar foambased discs reported in the literature including carbon foams derived from tar pitch [28,45], mesophase pitch [27], PAA resin [26] as well as a mixture of mesophase pitch and mesocarbon microbeads [34]. To our knowledge the measured strength of 56 ± 3 MPa for ACDMP1C2 places this carbon foam among the strongest pitch or resin derived carbon foams reported in the literature, and ACDMP1C2 has a very high strength to density ratio (62 MPa·g -1 cm 3 ).…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…These stress-stain measurements show that although mesophase pitch to coal ratio did not have a significant effect on the density or total porosity of the KOH activated ACDs (refer to Table 2), the amount of coal added did have a strong influence on compressive strength of the discs with the compressive strength of ACDMP1C2 (56 ± 3 MPa) prepared with the highest concentration of coal particles more than twice the strengths measured for ACDMP1C1 (27 ± 1 MPa) and ACDMP2C1 (24 ± 2 MPa). In fact, as shown in Table 3 all three KOH activated MP + coal ACDs produced in this study exhibited much greater compressive strengths than similar foambased discs reported in the literature including carbon foams derived from tar pitch [28,45], mesophase pitch [27], PAA resin [26] as well as a mixture of mesophase pitch and mesocarbon microbeads [34]. To our knowledge the measured strength of 56 ± 3 MPa for ACDMP1C2 places this carbon foam among the strongest pitch or resin derived carbon foams reported in the literature, and ACDMP1C2 has a very high strength to density ratio (62 MPa·g -1 cm 3 ).…”
Section: Resultssupporting
confidence: 52%
“…In these experiments, changing the MP : coal ratio from 1:2 to 2:1 did not have a significant effect on the skeletal density or total porosity of the ACDs. The skeletal density of each of these ACDs is within the measurement uncertainty of the skeletal densities of coal particles activated with KOH at the same furnace conditions (1.92 ± 0.24 g·cm 3 ) [43] . The bulk densities of the ACDs shown in Table 2 ) [44].…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations